Reducing rates of operative intervention for pediatric post‐tonsillectomy hemorrhage. (4th January 2018) - Whelan, Rachel L.; Shaffer, Amber; Anderson, Martin E.; Hsu, Jessica; Jabbour, Noel
Abstract : Objectives/Hypothesis: The aims of this study were to determine the frequency of rebleeding in patients admitted for observation after presentation for nonactive hemorrhage in the post‐tonsillectomy period, compare rebleeding rates between patients managed with observation versus initial operative control, and describe the complication profile associated with observation as a management strategy for post‐tonsillectomy bleeding. Study Design: Case series with retrospective review of patients. Methods: Patients presenting from September 1, 2013 to August 31, 2015 for post‐tonsillectomy hemorrhage to a tertiary pediatric care center were evaluated for inclusion in the study. Inclusion criteria included patients ≤18 years of age without active bleeding at the time of the initial examination. Proportions were compared using χ 2 and Fisher exact tests, whereas continuous data were compared using the Wilcoxon rank sum test. Results: Of 3, 866 tonsillectomy patients, 285 (7.4%) presented with concern for oropharyngeal bleeding in the postoperative period, of whom 224 were admitted for nonactive bleeding. Of patients with nonactive bleeding, 203 (90.6%) were managed with observation and 21 (9.4%) with operative intervention. Rate of rebleeding was 26/203 (12.8%) after inpatient observation and 3/21 (14.3%) after operative intervention ( P  = 1.000). Frequency of rebleeding requiring operative control in patients undergoing initial observation was 14/203 (6.9%). Conclusions: In our pilot study, rates of rebleeding in patients observed for nonactive post‐tonsillectomy hemorrhage was not statistically different than those managed with initial operative exploration. Although preliminary in nature, our data suggest observation may have comparable safety and efficacy when compared to operative management for pediatric patients presenting with nonactive post‐tonsillectomy bleeding. Further data collection to establish an optimal management algorithm is ongoing. Level of Evidence: 4 Laryngoscope, 1958–1962, 2018